Impacts of Sustainable Tourism in Porto and North of Portugal: A Literature Review on Post-Covid Evolution and Implications - Nuno MACHADO; António B. COELHO; Paulo GONÇALVES; Pedro LIBERATO (Communications of International Proceedings, 2023)
This research delves into the post-COVID evolution of sustainable tourism in Porto and North of Portugal, aiming to shed light on critical aspects for industry stakeholders and researchers. The motive behind this study lies in the imperative to understand the shifts in tourism dynamics and their implications for the region's sustainability, catalyzed by the transformative impacts of the pandemic and challenges posed by mass tourism. With the surge in awareness, the study explores the need to reconcile economic development with environmental preservation and the well-being of local communities. Addressing a void in the literature, our focus extends beyond the immediate effects of the pandemic, emphasizing the evolving landscape of sustainable tourism. The study's significance lies in providing insights into the trends, challenges, and opportunities that have emerged in the region. Methodologically, a narrative literature review allows us to synthesize existing knowledge, offering a nuanced perspective on the subject. This approach enables a holistic analysis of the sustainable tourism landscape, considering both the successes and challenges faced by the region. Our findings indicate a positive shift towards sustainability, marked by a reduction in seasonality rates and a transition from coastal mass tourism to a more sustainable inland tourism model in rural areas. These findings signify a promising direction for future tourism development in the region. Summarily, this study provides valuable insights into the post-COVID evolution of sustainable tourism in Porto and North of Portugal, addressing a critical gap in the literature and providing practical implications for industry professionals and researchers.
Keywords: sustainable tourism; sustainable tourism marketing; Porto and North of Portugal; post-COVID evolution